Analysis of Serum Interleukin (IL)-1β and IL-18 in Systemic Lupus Erythematosus - Mende, Rachel; Vincent, Fabien B.; Kandane-Rathnayake, Rangi; Koelmeyer, Rachel; Lin, Emily; Chang, Janet; Hoi, Alberta Y.; Morand, Eric F.; Harris, James; Lang, Tali (Frontiers in Immunology, 2018)
Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disease characterised by biological and clinical heterogeneity. The interleukin (IL)-1 superfamily is a group of innate cytokines which contribute to pathogenesis in many autoimmune diseases. IL-1b and IL-18 are two members that have been shown to play a role in murine lupus-like models, but their role in human SLE remains poorly understood. Here, IL-1b and IL-18 was quantified by ELISA in the serum of healthy controls and SLE patients from a prospectively followed cohort. Disease activity and organ damage were assessed using SLE disease activity index 2000 (SLEDAI-2K) and SLE damage index scores (SDI), respectively. 184 SLE patients (mean age 44.9 years, 91% female, 56% dsDNA positive) were compared to 52 HC. SLE patients had median [IQR] SLEDAI-2K of 4 [2,6], and SDI of 1 [0-2]. Serum IL-18 levels were statistically significantly higher in SLE patients compared to healthy controls. Univariable linear regression analyses showed that patients with active renal disease or irreversible organ damage had statistically significantly elevated serum IL-18 levels. The association between serum IL-18 and active renal disease was confirmed in multivariable analysis after adjusting for ethnicity and organ damage. High baseline serum IL-18 levels were associated with organ damage at the subsequent visit. Serum IL-1b levels were not significantly elevated in SLE patients when compared to healthy controls, and had no association with overall or organ-specific disease activity or organ damage in cross-sectional and longitudinal analyses. Our data suggests that serum IL-18 and IL-1b have different clinical implications in SLE, with IL-18 being potentially associated with active renal disease.